Student Learning in a Multimedia-based Constructivist Learning Environment - Doris U. Bolliger (International Journal of Instructional Technology, 2022)
It has been suggested in the existing literature that the use of constructivist approaches in the educational setting contributes to active learning and knowledge transfer for students. This paper provides an overview of constructivist approaches used in a graduate-level instructional media production course at a midwestern comprehensive university. Qualitative data collection techniques were used to investigate the perceptions and learning of students in an environment in which both students and content were the center of the learning experience. The findings suggest the use of active learning approaches, in which students have the opportunity to interact with peers and the instructor, discussion and reflection on learning experiences, and encouragement of knowledge sharing, contribute to student learning.